Peranan Dayak cultural foundation (DCF) dalam memelihara tarian ngajat - Suting, J.H (Universiti Malaysia Sarawak, UNIMAS, 2007)
The purpose of this research is to ascertain the role of the Dayak Cultural Foundation in preserving the traditional dance of the Iban, the ngajat dance, which is slowly being forgotten. The researcher will touch on the efforts by the Dayak Cultural Foundation in ensuring that ngajat dance will survive and showcase the uniqueness of Iban culture and arts.